Protocol for a systematic review and meta-analysis of culturally adapted internet- and mobile-based health promotion interventions. Issue 11 (9th November 2020) - Balci, Sumeyye; Spanhel, Kerstin; Sander, Lasse; Baumeister, Harald
Abstract : Introduction: High rates of immigration pose challenges for the healthcare systems of many countries to offer high-quality care to diverse populations. Advancing health interventions with incorporating the cultural background of diverse populations can be helpful to overcome this challenge. First studies suggest that culturally diverse populations might benefit from culturally adapted internet-based and mobile-based interventions (IMI) to promote health behaviours. However, the effectiveness of culturally adapted IMIs for health promotion interventions has not been evaluated systematically. Therefore, the aim of this review is to assess the effectiveness of culturally adapted IMIs regarding health promotion. Additionally, the cultural adaptation features of these interventions will be outlined. Methods and analysis: Randomised controlled trials (RCTs) investigating the effectiveness of culturally adapted IMIs to promote health behaviours in the field of healthy eating, smoking cessation, alcohol consumption, physical activity and sexual health behaviour will be identified via a systematic search of the databases MEDLINE, Embase, PsycINFO, CENTRAL. The preliminary search has been conducted on the 26 August 2019 and will be updated in the process. Data will be pooled meta-analytically in case of at least three included studies reporting on the same outcome. Moreover, a narrative synthesis of the included studies will be conducted. The risk of bias will be assessed using the Cochrane Collaboration's tool for the Quality Assessment of RCTs V. 2.0. Publication bias will be assessed using funnel plots. Ethics and dissemination: Ethical approval is not required for this study. The results of this study will be published in a peer-reviewed international journal. PROSPERO registration number: PROSPERO; CRD42020152939